2021
DOI: 10.3390/horticulturae7120516
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Profile Characterization of Commercial Peach (Prunus persica) Cultivars Grown in Georgia, USA

Abstract: Peach production in Georgia, USA, extends from mid-May to mid-August. Multiple cultivars are commercially grown in the U.S., and each cultivar has unique fruit quality characteristics, which could influence consumer perception and acceptability. Among those, peach flavor has been minimally characterized among cultivars. Headspace-solid phase microextraction (HS–SPME) combined with gas chromatography–mass spectrometry (GC–MS) was used to characterize the volatile profile of 42 peach cultivars commercially grown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 22 publications
0
8
1
Order By: Relevance
“…Considering their abundance, the most important aldehydes for the WF and FP are (E)-2-hexenal, hexanal, heptanal, and nonanal. Contrary to the current results, benzaldehyde was identified as a major aldehyde contributor in a study of American peach cultivars [ 3 ]. Heptanal has its highest quantity in the early-ripening variety “Filina”.…”
Section: Resultscontrasting
confidence: 98%
See 2 more Smart Citations
“…Considering their abundance, the most important aldehydes for the WF and FP are (E)-2-hexenal, hexanal, heptanal, and nonanal. Contrary to the current results, benzaldehyde was identified as a major aldehyde contributor in a study of American peach cultivars [ 3 ]. Heptanal has its highest quantity in the early-ripening variety “Filina”.…”
Section: Resultscontrasting
confidence: 98%
“…It should also be mentioned that the fruit pulp contains more lactones compared to the whole fruit. Γ-Dodecalactone is also a major lactone isolated in other research [ 3 ]. Lactones, particularly delta-lactones, are as well implicated in the peach aroma.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different conclusions can be made based on the methods used for collection, the compound concentrations, and the nature of the volatiles produced by fruit. A recent study confirmed significant differences in the number of identified compounds and their quantities exist [23].…”
Section: Resultsmentioning
confidence: 73%
“…Baking defatted tiger nut flour generated γ-undecanolactone, and its relative content gradually increased, enhancing peanut and nutty aromas. γ-Undecanolide (peach aldehyde) was the aroma of the raw material itself, and its relative content rose after baking for 8 min, with coconut and peach-like aromas [33]. γ-Butyrolactone is formed after roasting and has a nutty aroma, resulting from the esterification of hydroxy fatty acids or the oxidation of unsaturated aldehydes.…”
Section: Vocs In Defatted Tiger Nut Flourmentioning
confidence: 99%